Biochemistry, Doppler echocardiography, and electrocardiography evaluation in captive owl monkeys (Aotus sp) - Teixeira, Andr? Luis de Souza (Wiley, 2021)
Background: The cardiovascular system of owl monkeys has been studied due to frequent postmortem findings of heart disease in asymptomatic animals. The silent aspect and the difficulty of early diagnosis intensify the importance of studying the cardiovascular system in this species. Methods: Echocardiogram evaluation was carried out on 60 animals, grouped into suspect or non-suspect of having heart diseases, and evaluated through electrocardiogram, hematology, and biochemical tests. Results: Doppler echocardiography indicated two animals with suspicion of left ventricular hypertrophy and eight with dilated cardiomyopathy. Suspect animals had higher cardiac measurements and reduced shortening fraction. Troponin I was detectable in two animals (0.128 ng/mL and 0.584 ng/mL), and serum albumin concentration was significantly higher in non-suspect animals (P <.05). Conclusions: The importance of echocardiographic measurements of IVSd, IVSs, LVIDd, LVIDs, LVPWd, LVPWs, LA, EF, and FS in the cardiac evaluation of captive owl monkeys was evidenced.